Optimization Of Geophysical Design Survey Priority Areas For Unconventional Oil And Gas Exploration Using Topex Gravity Data Analysis - Dianwiyono, Yustisio; Wiradityo, Dhiyatamma Purusa (Jurnal Pendidikan Indonesia, 2025)
The exploration of unconventional oil and gas resources requires efficient identification of priority areas with high hydrocarbon potential and reduced exploration risk. This study aims to optimize geophysical survey design by integrating TOPEX gravity data analysis with geological interpretation techniques. The TOPEX satellite gravity dataset was processed and filtered to delineate subsurface density anomalies that may indicate structural traps, fault zones, and basin configurations associated with hydrocarbon accumulation. Quantitative interpretation was carried out using spectral analysis and derivative filtering methods to enhance shallow and deep anomaly features. The integration of gravity anomalies with regional geological data enabled the identification of priority zones for further seismic and drilling investigations. Results show that TOPEX gravity data provides a cost-effective and reliable approach for delineating potential unconventional reservoirs, particularly in frontier or data-limited regions. The optimized geophysical survey framework proposed in this research can serve as a strategic tool for national energy exploration programs, ensuring efficient resource allocation and improved success rates in unconventional hydrocarbon exploration.